VD_FINDINFO MP / 2024 / 7 vom 30. Dezember 2024 - VD Tribunal cantonal (2024)
CONTRAT DE LICENCE, DÉBAUCHAGE, DÉNIGREMENT | 2 LCD, 3 al. 1 let. a LCD, 4 let. a LCD, 4 al. 2 LCart, 7 LCart, 17 CPC (CH)